Geotechnical Characteristics and Management of Clay Soil for Enhanced Road Construction - Michael, Frido (IHSA Institute, 2024)
This research investigates the geotechnical characteristics of clay soil and their implications for road construction. Clay soils present significant challenges due to their low bearing capacity, high compressibility, and susceptibility to swelling and shrinkage. The study aims to analyze these properties in detail, evaluate effective soil stabilization techniques, and assess advanced drainage solutions and predictive modeling tools. Through a comprehensive methodology that includes site selection, sample collection, laboratory testing, and data analysis, the research provides valuable insights into the behavior of clay soils under various conditions. Key findings reveal that while traditional stabilization methods, such as lime and cement, remain effective, newer materials like fly ash offer enhanced performance. Advanced drainage technologies, including geocomposites and prefabricated vertical drains (PVDs), have proven superior in managing soil moisture and preventing water-related issues. The research also demonstrates that modern compaction techniques and geosynthetics can significantly reduce soil compressibility and settlement. The implications of these findings are profound for the construction industry, offering practical recommendations for improving the durability and performance of roadways on clay soils. The study highlights the need for advanced stabilization, effective drainage solutions, and refined predictive modeling to address the challenges of clay-rich substrates.